1998
DOI: 10.3354/dao034021
|View full text |Cite
|
Sign up to set email alerts
|

Performance of serum-free broth media for growth of Renibacterium salmoninarum

Abstract: Growth of Renibacterium salmoninarum was compared in 14 different broth media; 13 serum-free, and 1 that contained newborn calf serum, KDM2+M. Supplementation with 1 % v/v R. salmoninarum MC04M metabolite was evaluated for 6 of the media that do not utilize it as part of their ingredients. Viable cells were enumerated on Days 10, 20, and 30 post inoculation to evaluate performance. The experiment was repeated 3 times using high, low, and medium (trials 1 to 3, respectively) cell concentrations as inoculum. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…These modifications combined the observations that each of these supplements enhance and/or select R. salmoninarum growth [14][15][16]20]. The modified medium will be referred to as the modified KDM2 (MKDM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These modifications combined the observations that each of these supplements enhance and/or select R. salmoninarum growth [14][15][16]20]. The modified medium will be referred to as the modified KDM2 (MKDM).…”
Section: Methodsmentioning
confidence: 99%
“…The improved growth was attributed to metabolites secreted by the initial culture. Using the same concept, Teska [15] and Starliper et al [16] incorporated R. salmoninarum spent medium (1% v/v) into KDM2 for related BKD studies. While these modifications have supported the subculturing of previously isolated R. salmoninarum strains, direct isolation from infected tissues, particularly from carrier fish, yielded inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…salmoninarum is a gram-positive diplococcobacillus that grows very slowly and has fastidious nutritional requirements (8,12,39,40). R. salmoninarum produces abundant quantities of an extracellular, 57-kDa protein called p57 or major soluble antigen (MSA) (7,17,41).…”
mentioning
confidence: 99%
“…In Germany, BKD was first recorded in farmed salmon and trout by Hoffmann et al (1984) and has since been reported elsewhere in Europe, Japan, South America and many states of the USA. R. salmoninarum is a small, Gram-positive, nonmotile diplobacillus that has fastidious nutritional requirements (Austin et al 1983, Daly & Stevenson 1993, Teska 1994, Starliper et al 1998). Acute BKD is characterized by dark colouration of the fish, bloody ascites, exophathalmia, and granulomatous lesions of internal organs such as the kidney, whereas asymptomatic carriers can complete an entire life cycle and successfully spawn (Fryer & Lannan 1993).…”
Section: Introductionmentioning
confidence: 99%